2014
DOI: 10.1080/01431161.2014.958248
|View full text |Cite
|
Sign up to set email alerts
|

Typhoon-enhanced upwelling and its influence on fishing activities in the southern East China Sea

Abstract: Ocean-atmosphere interactions before and after the passage of Typhoons Haitang, Fung-wong, and Morakot across the southern region of the East China Sea (ECS) were examined by assessing satellite measurements of sea surface temperature (SST) and chlorophyll-a (chl-a) concentration in conjunction with wind data. In terms of the satellite-derived data, the SST declined and chl-a concentration increased after the passage of the typhoons, and this could have resulted from the upwelling induced by typhoons via their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…In addition to the influence on SST and Chl‐a, typhoons are found to be important for increasing fish abundance and influencing fish species composition (Chang et al, 2014; Yu et al, 2013). Thus, a comprehensive study on the responses of the ocean surface to typhoonscan improve our understanding of marine ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the influence on SST and Chl‐a, typhoons are found to be important for increasing fish abundance and influencing fish species composition (Chang et al, 2014; Yu et al, 2013). Thus, a comprehensive study on the responses of the ocean surface to typhoonscan improve our understanding of marine ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…This kind of typhoon‐induced bloom often appears along or to the right of the typhoon track a few days after the passage of the typhoon and lasts for 1–2 weeks at the surface layer or even more than 3 weeks in the subsurface layer [ Ye et al ., ]. Moreover, the ocean‐atmosphere interactions and fisheries data collected before and after the passage of several typhoons across the southern region of the ECS suggested that typhoons can enhance upwelling that results not only in increases of Chl a but also in changes of local fish communities and, consequently, fishing activities [ Chang et al ., ]. Typhoon‐induced upwelling can indeed stimulate efficient particulate organic carbon export out of the euphotic zone [ Shih et al ., ].…”
Section: Progress Of Upwelling Studies In the China Seasmentioning
confidence: 99%
“…It has been suggested that global warming may increase the frequency of strong typhoons (Emanuel 2005;Webster et al 2005), and consequently temperate, coastal communities would increasingly be exposed to such severe disturbances. However, only a few studies refer to the effects of typhoons on fishery activities in subtropical and temperate, coastal bays (Kawabata et al 2010;Yu et al 2013Yu et al , 2014Chang et al 2014). Additionally, as far as I knew, there is no information about the impact of a typhoon on changes in species composition obtained from purse seine fishing.…”
Section: Introductionmentioning
confidence: 99%